2018
DOI: 10.1016/j.jmoldx.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

External Quality Assessment Identifies Training Needs to Determine the Neoplastic Cell Content for Biomarker Testing

Abstract: Neoplastic cell content determination is crucial for biomarker testing. It is known that interobserver variation exists, but largescale data are missing about variation in tumor delineation and cell content determination. Results were obtained from the external quality assessment program for metastatic colorectal cancer from the European Society of Pathology (N = 5776 observations). The study included three parts: current practices were surveyed, neoplastic cell content estimations and delineations were retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 27 publications
(23 reference statements)
4
24
0
Order By: Relevance
“…Several studies have already shown significant variation in NCP estimates; on average, as high as 20% between different pathologists . This was recently confirmed by a large European‐wide study, which also identified large differences in the processes related to the estimation of the NCP, such as contouring the tumour area and macrodissection . In addition, this study identified problems with interpreting the NCP.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…Several studies have already shown significant variation in NCP estimates; on average, as high as 20% between different pathologists . This was recently confirmed by a large European‐wide study, which also identified large differences in the processes related to the estimation of the NCP, such as contouring the tumour area and macrodissection . In addition, this study identified problems with interpreting the NCP.…”
Section: Introductionsupporting
confidence: 61%
“…Accurate estimation is extremely important to correctly interpret the results of a molecular analysis which, in turn, is crucial for treatment decision‐making. Inaccurate estimations may impact upon patient outcomes . The present study proposes recommendations for standardising the processes related to defining the tumour area for macrodissection and for estimating the neoplastic cell percentage within this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that 13% of cases were denoted as insufficient materials is surprising, as the materials were carefully validated beforehand and verified to contain sufficient neoplastic cells lacking tumor heterogeneity, and other peers were able to successfully analyze these cases in the same scheme. Indeed, pre-analytical variables such as the estimation of the neoplastic cell content has previously been linked to deviations in mCRC EQA results [ 29 ]. As the samples in the EQA scheme consisted of pre-cut and labelled samples, laboratories should therefore be extra cautious as other pre-analytical issues could arise in routine practice during sample reception, storage, and preparation.…”
Section: Discussionmentioning
confidence: 99%
“…To relate the NGS detected gains to FISH detected gains, the calculated number of alleles could be corrected for the estimated percentage of neoplastic nuclei in the area from which the gDNA was isolated. While we realize the estimation of this percentage is error-prone [ 14 , 15 ], it can be supported by the variant allele frequencies (VAF) of somatic variants in other genes and it allows estimation of the number of gene copies in the “order of magnitude” required to asses clinical relevance. As mentioned above, the estimation of the actual copy number gains may be biased in highly aneuploid tumors.…”
Section: Clinically Relevant Measures Of Gene Amplificationmentioning
confidence: 99%